2016
DOI: 10.1371/journal.pone.0145236
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Ferulic Acid against Heat Stress-Induced Intestinal Epithelial Barrier Dysfunction In Vitro and In Vivo

Abstract: Heat stress is important in the pathogenesis of intestinal epithelial barrier dysfunction. Ferulic acid (FA), a phenolic acid widely found in fruits and vegetables, can scavenge free radicals and activate cell stress responses. This study is aimed at investigating protective effects of FA on heat stress-induced dysfunction of the intestinal epithelial barrier in vitro and in vivo. Intestinal epithelial (IEC-6) cells were pretreated with FA for 4 h and then exposed to heat stress. Heat stress caused decreased t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 41 publications
5
48
0
Order By: Relevance
“…In addition, TJ‐related proteins are involved in the maintenance of paracellular permeability and barrier function, which are necessary for defense against pathogenic bacteria (Bondow, Faber, Wojta, Walker, & Battle, 2012). In vitro and in vivo studies have shown that heat exposure induces disruption of the intestinal integrity (Groschwitz & Hogan, 2009; He et al, 2016), and our results, which showed that heat‐exposure induced a decrease in the TEER values and increases in the FS flux and efflux ratio, were consistent with these previous studies. Likewise, the protein expression of ZO‐1, occludin, and claudin‐1 was significantly reduced in IPEC‐J2 cells exposed to heat for 72 hr.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, TJ‐related proteins are involved in the maintenance of paracellular permeability and barrier function, which are necessary for defense against pathogenic bacteria (Bondow, Faber, Wojta, Walker, & Battle, 2012). In vitro and in vivo studies have shown that heat exposure induces disruption of the intestinal integrity (Groschwitz & Hogan, 2009; He et al, 2016), and our results, which showed that heat‐exposure induced a decrease in the TEER values and increases in the FS flux and efflux ratio, were consistent with these previous studies. Likewise, the protein expression of ZO‐1, occludin, and claudin‐1 was significantly reduced in IPEC‐J2 cells exposed to heat for 72 hr.…”
Section: Discussionsupporting
confidence: 93%
“…Decreased expression of TJ proteins during heat stress was found in Caco‐2 cells (Gupta et al, ) and in animal studies (Wu et al, ). Inhibition of these proteins expression indicates the disturbance of the TJ barrier functions and accompanied by intestinal permeability (He et al, ). Our results showed that oral administration of S. cerevisiae fermentate to rats before heat stress significantly enhanced TJ proteins expression.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased expression of TJ proteins during heat stress was found in Caco-2 cells (Gupta et al, 2017) and in animal studies . Inhibition of these proteins expression indicates the disturbance of the TJ barrier functions and accompanied by intestinal permeability (He et al, 2016). Our results showed that oral administration of S. cerevisiae fermentate to rats before heat stress significantly ES-rats were orally gavaged with Saccharomyces cerevisiae fermentate and exposed to heat stress; EC-rats were orally gavaged with Saccharomyces cerevisiae fermentate and kept at room temperature; PS-rats were orally gavaged with PBS and exposed to heat stress; PC-rats were orally gavaged with PBS and kept at room temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Fetoni and others () provided functional in vivo evidence that FA limits noise‐induced hearing loss in the guinea‐pig, not only by its radical‐scavenging ability in the peritraumatic period, but also due to the upregulation of the cytoprotective enzyme heme oxygenase‐1 (HO‐1) in guinea‐pig cochleae. Further protective effects of FA have been recently described on kidneys (Alam and others ), the liver (Maruf and others ), intestine (He and others ), and pancreas (Roy and others ), among others.…”
Section: Antioxidant Properties Of Fa and The Relationship With Its Bmentioning
confidence: 84%